How to Detect Financial Shenanigans?: Evidence From the Healthcare Sector in Indonesia - Sakti, Eklamsia; Maduratna, Enggal Sari (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
This research aims to empirically test the ability of financial ratios to detect financial shenanigans during the Covid-19 pandemic. The objects of this research are healthcare companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2022. The research sample consisted of 72 financial report data. The data analysis technique uses logistic regression with IMB SPSS 25 statistical tool. Detection proxies use return on assets (ROA), revenues quality ratio (RQR) and Real Earnings Management (REM). The proxies for financial shenanigans are the Beneish M-score model and the Dechow F-score model. The results of this research are (1) ROA is significant for F score, (2) RQR is significant for F score, (3) REM is significant for M score. The main conclusion of This research is that financial ratios help detect financial shenanigans that occurred during the Covid-19 pandemic.